A Study on Factors influencing the adaptation of private labels in organized retail branding among Malaysians - Anniselam, Francis; Ng, Alex, Hou Hong (INTI International University, 2018)
With the growing realization that brand images are one of a firm’s most valuable intangible assets, branding has emerged as a top management priority in the last decade. Given its highly competitive nature, branding can be especially important in the retailing industry to influence customer perceptions and drive store choice and loyalty. Five major objectives to determine about the Factors influencing the adaptation of private labels in organized retail branding among Malaysians which are product quality, price, brand & packaging on influencing the purchasing pattern of retail brand. The price, quality, brand and packaging dimension of the private label products were tested on Malaysian consumers on comparing between two product dimension that is on retailers branding products and manufactures branding product. Meanwhile, the researcher was also determining on the relationship between all the independent variables. The research been conducted in qualitative method where 300 questionnaires were distributed via online Google form. Then, the data collected was further analysed with the analysis method of frequency table, independent t-test, and descriptive analysis. Meanwhile secondary data were also used for support with journals, reference books, articles and online data information as to achieve the valid of research